Mina Loy’s Surrealist Strategies of Renewal - Diane Drouin (Sillages Critiques)
In her essay “Modern Poetry,” published in the little magazine Charm in 1925, the British artist Mina Loy identified the source of the renewal of the English language in the streets of New York, famously claiming: “It was inevitable that the renaissance of poetry should proceed out of America, where latterly a thousand languages have been born.” The cosmopolitan avant-garde artist celebrates the “composite language” of the United States, and the ability of “the true American” to “ingeniously coin new words for old ideas.” However, although Loy’s poems may have been influenced by this American “renaissance of poetry,” her often overlooked prose autobiographies in prose – that she began in Paris in the 1920s and completed in New York in the 1940s – should be analyzed in the light of the Surrealist renewal of language. Throughout her life, Loy paid tribute to many prominent artists, including Gertrude Stein, Pablo Picasso, Marcel Duchamp, the sculptor Brancusi in her poem “Brancusi’s Golden Bird,” the German painter Richard Oelze, or the American Surrealist Joseph Cornell, who both appear in her Surrealist novel Insel. Relying on Loy’s lesser-known essays and notes on art, and on her own artworks, including her late assemblages, this article examines Loy’s linguistic, critical, spiritual, and material strategies of renewal. I argue that her critical takes on art are entwined with her own creative practices as a visual artist, combining Surrealist techniques and her innovative experimentations with recycling.